Features of the distribution and condition of phytoplankton at different depths in the Kislo-Sladkoe Lake partly isolated from the White Sea - D. N. Matorin; D. A. Todorenko; D. A. Voronov; S. N. Goryachev; L. B. Bratkovskaya; E. D. Krasnova; Д. Н. Маторин; Д. А. Тодоренко; Д. А. Воронов; С. Н. Горячев; Л. Б. Братковская; Е. Д. Краснова (Lomonosov Moscow State University, School of Biology, 2022)
Chlorophyll fluorescence methods were used for study of phytoplankton in the Kislo-Sladkoe Lake on the White Sea coast in 2018. In the chemocline (between aerobic and anaerobic zones) of the lake at a depth of 3.3 m a red water layer was observed with chlorophyll a concentration of 1.7 μg/L, despite the presence of hydrogen sulfide. This water layer was dominated by cryptophyte algae (Rhodomonas sp.), in which a high functional activity of the photosynthetic apparatus was observed in terms of the PIABS fluorescence parameter, expressed through high values of the quantum yield of the primary photochemical reaction in PS2 (FV / FM), the proportion of active RCs (RC/ABS), and the quantum yield of electron transport in PS2(φEo). Such a high functional activity of the photosynthetic apparatus of cryptophyte algae in the chemocline may indicate the resistance of cryptophyte algae to the presence of hydrogen sulfide. By comparison, the phytoplankton in the surface water layer showed lower photosynthetic activity. Experiments with photoinhibition showed that the chemocline phytoplankton community is characterized by a greater reparative capacity after photooxidative stress despite the increased photosensitivity. Application of chlorophyll fluorescence methods for study of the state of phytoplankton in stratified meromictic water bodies is proposed. Флуоресцентные методы были применены в исследовании фитопланктона стратифицированного озера Кисло-Сладкое на беломорском побережье в 2018 г. В хемоклине водоема (на границе аэробной и анаэробной зон) на глубине 3,3 м наблюдался красный слой воды с концентрацией хлорофилла а 1,7 мкг/л. В этом слое воды доминировали криптофитовые водоросли (Rhodomonas sp.), у которых зафиксирована высокая активность фотосинтетического аппарата по параметрам флуоресценции (PIABS), выраженная через высокие значения квантового выхода первичной фотохимической реакции в фотосистеме 2 (FV / FM), доли активных реакционных центров (РЦ) (RC/ABS) и квантового выхода электронного транспорта в ...